2021
DOI: 10.1108/compel-01-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a simplified hybrid algorithm for short-term load forecasting in a power system network

Abstract: Purpose The purpose of this paper is to develop a hybrid algorithm, which is a blend of auto-regressive integral moving average (ARIMA) and multilayer perceptron (MLP) for addressing the non-linearity of the load time series. Design/methodology/approach Short-term load forecasting is a complex process as the nature of the load-time series data is highly nonlinear. So, only ARIMA-based load forecasting will not provide accurate results. Hence, ARIMA is combined with MLP, a deep learning approach that models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, it has been widely confirmed that, the performances of these components are prone to be affected by parasitic parameters such as inter-electrode capacitance and resistance (Allagui et al , 2021), and prone to be affected by parameter drift phenomenon, which is in direct contact with some dynamic characteristics of MOSFETs (Chen et al , 2020; Mukunoki et al , 2018a, 2018b), Miller plateau and oscillations at the turn on/off moments, to name a few. Therefore, a reasonable and accurate model has a pivotal role in the performance analysis of both MOSFETs and circuit systems with such components (Palanichamy and Balamurugan, 2014; Mayilsamy et al , 2021; Hsu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been widely confirmed that, the performances of these components are prone to be affected by parasitic parameters such as inter-electrode capacitance and resistance (Allagui et al , 2021), and prone to be affected by parameter drift phenomenon, which is in direct contact with some dynamic characteristics of MOSFETs (Chen et al , 2020; Mukunoki et al , 2018a, 2018b), Miller plateau and oscillations at the turn on/off moments, to name a few. Therefore, a reasonable and accurate model has a pivotal role in the performance analysis of both MOSFETs and circuit systems with such components (Palanichamy and Balamurugan, 2014; Mayilsamy et al , 2021; Hsu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%